Pengaruh Teknologi Informasi Dan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Perusahaan (Studi Pada PT. Mitra Pinasthika Mustika Tbk) - Ana Lailatul Arofiyah; Kafidin Muzakki (Majalah Ekonomi, 2024)
This study aims to 1.) determine the effect of information technology on the quality of the company's financial statements at PT Mitra Pinasthika Mustika Tbk. 2.) determine the effect of the accounting information system on the quality of the company's financial statements at PT Mitra Pinasthika Mustika Tbk. 3.) determine the effect of information technology and accounting information systems on the quality of the company's financial statements at PT Mitra Pinasthika Mustika Tbk. The research method used in this research is descriptive quantitative method with the help of SPSS (Statistical Program for Social Science) analysis tool. The results of this study indicate that the influence of Information Technology and Accounting Information Systems has a significant influence on the company's financial statements at PT Mitra Pinasthika Mustika tbk.